Analysis of efficiency of spur ground gears and the influence of running-in. (January 2016) - Sjöberg, S.; Sosa, M.; Andersson, M.; Olofsson, U.
Abstract: High-performing gear transmissions are needed to reduce CO2 emissions. In this paper an FZG gear test rig was used to investigate how two running-in loads affect the gear mesh efficiency for two different temperatures. The gear surface roughness was investigated in parallel with testing. Higher efficiency was observed for tests using a high running-in load, and for low lubricant temperatures. The running-in load had a larger effect on the mesh efficiency than temperature. The high running-in load also yielded higher gear mesh efficiency and had a larger impact on surface parameters. Highlights: The mesh efficiency of running gears was affected by different running-in loads. A high running-in load resulted in higher gear mesh efficiency. The scatter in mesh efficiency response was lower using a high running-in load. The high running-in load had a larger effect on surface roughness parameters.